2018
DOI: 10.1038/s41598-018-19740-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between H-type Hypertension and Asymptomatic Extracranial Artery Stenosis

Abstract: Asymptomatic extracranial artery stenosis (ECAS) is a well-known risk factor for stroke and H-type hypertension, which is defined as hypertension with hyperhomocysteinemia, is associated with cardio-cerebrovascular diseases. However, the impact of H-type hypertension on ECAS is mostly unknown. We designed this study to investigate the association between H-type hypertension and prevalence of ECAS. We included 2330 participants in this study and classified them into four groups: the control group without hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…As a result, blood pressure increases. [ 18 , 20 ] Many studies have shown that Hcy is associated with elevated blood pressure. [ 5 , 17 , 18 , 20 ] For every 5 μmol/L increase in Hcy, the SBP and DBP increase by 0.7/1.2 mm Hg and 0.5/0.7 mm Hg in women and men, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, blood pressure increases. [ 18 , 20 ] Many studies have shown that Hcy is associated with elevated blood pressure. [ 5 , 17 , 18 , 20 ] For every 5 μmol/L increase in Hcy, the SBP and DBP increase by 0.7/1.2 mm Hg and 0.5/0.7 mm Hg in women and men, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 20 ] Many studies have shown that Hcy is associated with elevated blood pressure. [ 5 , 17 , 18 , 20 ] For every 5 μmol/L increase in Hcy, the SBP and DBP increase by 0.7/1.2 mm Hg and 0.5/0.7 mm Hg in women and men, respectively. [ 49 ] In addition, in 2016, a meta-analysis of 11 published epidemiological studies demonstrated that Hcy contributed to the risk of essential hypertension (OR = 1.36, 95% CI: 1.02–1.80, random-effects model).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, serum homocysteine was significantly associated with carotid artery stenosis in internal carotid arteries and external carotid arteries as well as the degree of stenosis [83,84]. The hypertensive patients who had raised serum homocysteine were reported to have higher risk of developing asymptomatic extracranial carotid artery stenosis [85]. However, other studies showed conflicting results [86][87].…”
Section: Homocysteine and Extracranial Carotid Artery Stenosismentioning
confidence: 97%
“…Assessment of H-type hypertension H-type HTN was defined as HTN combined with HHcy [19]. The blood pressure of each participant was twice measured by a mercury sphygmomanometer, and the average of the 2 readings was calculated.…”
Section: Study Design and Populationmentioning
confidence: 99%